A New Approach For Image Hiding Based On Contourlet Transform - Saeed Masaebi; Amir Masoud Eftekhary Moghaddam (International Journal of Electrical and Computer Engineering (IJECE), 2012)
A new image hiding method based on the contourlet transform is proposed inthis paper. This strategy is based on storing information in high frequency subbands of contourlet transform. The embedding approach is in direction that the contourlet sub-bands have the least statistical disorder. As a result, the proposed algorithm has a higher robustness against to common steganalysis approaches. In addition, the quality of stegano image has considerably improved in comparison with related state of the art methods, with the extracted secret image having an acceptable quality. Furthermore, theexperimental results show robustness respect to Gaussian noise and otherattacks such as JPEG compression.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1433